EP270 Adenocarcinoma (ADK) with clear cells of the uterine cervical collar in an young girl in connection with one case. (1st November 2019) - Hadjarab, F; Chekman, CE; Taibi, A; Bouzid, K
Abstract : Introduction/Background: ADK of the uterine collar with cells clear is veryrare in the young woman, among the risk factorsone brings back the catch de DISTILBENE, Diéthylstilbestrol at the mom, whereas cancer epidermoïde of the collar the principal disease-causing agent is the papilloma virus HPV, herforecast is pejorative. We report in this poster anobservation illustrating this rare situation withreview of the literature. Methodology: Young girl S.A 22 years old single person;virgin with ATCD of catch by the mother of inductor of ovulation.The patient with presented métrorragies andthe initial gynaecological examination toobjectified a small mass of the collar bleedingin contact with 3cm of diameter, a biopsy ofthe mass to aim diagnosis at summer carried out whose histological results returned in favor of clear ADK with cells of the uterine collar. Results: Treated by standard RT then surgery CHEL.Cost after 6 months with pulmonary andosseous metastases. having profited from several lines of chemotherapy of which thefirst: Adriamycine/CDDP after 6 curesdevelopment of cerebral localization, irradiated then a second-row forward of chemotherapy (CT): CPM/ Bévacizumab after 7 months of treatment, progression of metastases. The young patient received two other lines of CT. Deceased after 42 month of the beginning of the treatment following a renal insufficiency; respiratory. Conclusion: Clear ADK of the uterine cervical collar in the young girl remains very rare; with absence of known factors predisposing with a therapeutic forecast péjoratif. la answer is overall, non satisfactory that it is the radiotherapy or chemotherapy. Disclosure: No conflict interest.